EQCM verification of the concept of drug immobilization and release from conducting polymer matrix. (10th September 2016) - Krukiewicz, Katarzyna; Bednarczyk-Cwynar, Barbara; Turczyn, Roman; Zak, Jerzy K.
Highlights: Disuccinyl derivative of anti-cancer drug, betulin, was immobilized in PEDOT matrix. EQCM was used to monitor the processes of drug immobilization and release. SEM, EDS and IR confirmed the presence of drug in polymer matrix. The release of drug was performed with and without application of external potential. Potentiodynamic stimulation was more efficient that potentiostatic release. Abstract: Local drug delivery based on conducting polymer carriers is an innovative approach of medical treatment joining the concept of regional release of biomolecules with ion-exchange properties of conjugated polymers. In this study, we have applied electrochemical quartz crystal microbalance (EQCM) to monitor the process of three-step immobilization and release of anti-cancer drug, disuccinyl derivative of betulin, in PEDOT matrix. Each step of this process has been carefully investigated, i.e. electrochemical polymerization of monomer in the absence of drug, removal of primary dopant during the process of matrix reduction and drug incorporation during the process of matrix oxidation. The release of drug from PEDOT matrix has been performed via three paths, i.e. spontaneous release with no application of external potential, active release under potentiostatic conditions and active release under potentiodynamic conditions. EDS elemental analysis, scanning electron microscopy, IR and Raman spectroscopies, have been used to analyze structural and surface properties of drug-loaded PEDOT matrices.